Microsoft SharePoint 2010 enterprise applications on Windows Phone 7 : create enterprise-ready websites and applications that access Microsoft SharePoint on Windows Phone 7 /: create enterprise-ready websites and applications that access Microsoft SharePoint on Windows Phone 7. (2011) - Unknown
No abstract available